Electrical Grounding and Bonding, 6th Edition - Phil Simmons (Cengage Learning, 2020)
Completely updated to reflect the 2020 National Electrical Code, Simmons' ELECTRICAL GROUNDING AND BONDING, Sixth Edition provides a practical guide to the latest requirements in both Article 250 and Chapter 5 of the NEC along with current industry best practices. Clear explanations, real-world examples and colorful illustrations help you master and apply key electrical concepts, such as calculating conductor sizes, reading and interpreting NEC tables, using grounded conductor connections in AC systems, managing installations and sizing, and applying ""green"" practices for energy efficiency and environmental sustainability. Whether you are pursuing a degree program, professional training or an apprenticeship, this must-have resource equips you for career success. Important Notice: Media content referenced within the product description or the product text may not be available in the ebook version.